Encapsulation of Lactobacillus acidophilus in yeast cell walls (Saccharomyces cerevisiae) for improving survival in gastrointestinal conditions - Han, Le Nguyen; Van, Le Huynh Hong; Duc, Tran Van; Dao, Dong Thi Anh (Vietnam Journal of Science and Technology, 2016)
In search of high-quality health products, it is required that probiotic preparations consumed in gastro-intestinal condition remain metabolically active and preserve their activity. Several recent studies, consequently, have focused on probiotic protection via encapsulation in order to optimize probiotics’ viability as well as their delivery into gastro-intestinal environment. The objectives of this study were to find out a new material for encapsulation of probiotics, utilizing capsules prepared from Saccharomyces cerevisiae to protect living probiotic cells. The encapsulation of cells was achieved, using the crack scars of the yeast cell walls (YCW) created by the sonication method. Besides, some probiotic cells can be considered as being encapsulated by some surrounded yeast cells by direct cell-cell contact. It is concluded that thanks to encapsulation by yeast cells, probiotic’s metabolic activity and survival are markedly improved. This suggests a high potential in protecting probiotics from the extreme condition of digestion process and can be applied in protecting probiotic preparations in food formulations as well. It was found that encapsulation yield in this study reached its highest point at 82.008 ± 1.123%. Viability of encapsulated probiotic in simulated gastric juice (SGJ) after 150 minutes is 19.048 ± 2.701%, compared to that of free cells at 0%. Likewise, after a 4-hour treatment in simulated intestinal juice (SIJ) (0.5% bile salt) encapsulated probiotic proves better survival at 56.338 ± 5.094% than free cell at 43.677 ± 2.058%.